PEMBENTUKAN KARAKTER ANAK PADA LAGU TOKECANG, JAWA BARAT - Setiowati, Shintya Putri (Universitas Hasanuddin, 2020)
Indonesian culture is very diverse with forms ranging from dance, batik cloth, folklore, folk music and songs, traditional clothing, traditional houses, traditional food and drinks, traditional games, performing arts, rituals and so on. At the writing of this library research, the researcher focused on folk songs that are famous in West Java. The title song is Tokecang. The thing related to this song is that a simple song sung by children has a deep meaning. In this literature review, researchers associate Tokecang songs with the formation of children's characters. The formation of children's characters in the Tokecang song teaches that we, as social beings, must have an attitude of affection and social care. Affection is an emotional reaction to a person, animal, or object.